Obtaining a pure strain of bacterial cancer pathogen and studying its infectious activity in tree species under in vitroconditions - Baubekova А.К.; Abiyev, S.A.; Asilkhanova, R.Z. (Fundamental and Experimental Biology, 2022)
Dense and diverse primary forests, which nourish the soil, emit a large amount of oxygen, are the dream of every state. Therefore, the first President of Kazakhstan N. Nazarbayev ordered to make a large green zone around Nur-Sultan, which is being improved and refined every year. This project is designed to turn the capital of Kazakhstan, the city of Nur-Sultan, intoa green belt, completely sowing forests around thecity, the area of which is 100 thousand hectares. Properly grafted woody plants in the green belt, in addition to enriching the air with oxygen, decorating landscapes, should contribute to the ventilation of zones, the removal of polluted air from residential and industrial zones, the formation of vertical air flows andthe dispersion of polluted air in higher layers of the atmosphere, as well as air purification from various aerosols, dust, soot, and heat. Nevertheless, all these natural resources are under great threat due to the prevalence of a little-studied disease-bacterial cancer of tree species. Currently, such a disease is observed in Bashkortostan, the Baltic States, Tatarstan, the Republic of Adygea,the European part of Russia, as well as in Bryansk and adjacent regions. In these countries, the coverage of tree species with this disease is increasing, which creates a real threat of the tree trunks drying. Bacterial cancer of tree species is also found in Kazakhstan. In this regard, the study of this disease is relevant, since due to the characteristics of the lesion of trees, the diagnosis of the disease, forest-taxational and landscape conditions, its spread has not been fully studied. The purpose of our work is to take core samples from birch (Betula rendulaRoth.), which grows in the forests of the Green Belt surrounded by the city of Nur-Sultan, with signs of bacterial cancer (dropsy); obtain core samples from the trunk, to cultivate isolated bacterial cultures on nutrient media; to obtain pure strains of the causative agent of the disease, molecular identification of the nucleotide chain of ribosomal RNA 16S. In addition, the determination of the molecular characteristics of the obtained bacterial strains in accordance with the typical type of Dickeya dadantiion the international basis of Gene Bank. In the course of the study, the infectious activity of this strain of bacteria on other woody analogues was studied in vitro. Inoculation of birch leaves and catkins that have not undergone bacterial cancer with Dickeya dadantiistrains isolated by us in vitro showed complete virulence of the pathogen to the experimental birch population, i.e. infectious activity.